2014
DOI: 10.2334/josnusd.56.105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gutta-percha solvents on fiberglass post bond strength to root canal dentin

Abstract: The purpose of this study was to investigate the influence of gutta-percha solvents on the bond strength of fiberglass post to root canal dentin. Forty bovine incisors were decoronated, prepared, filled, and randomly distributed into four groups (n = 10) according to the gutta-percha solvent used: control, xylene, eucalyptol and orange oil. After root canal treatment, the posts were cemented into the prepared root canals using a resin-based cement. A micro pushout test was executed, and the patterns of failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…The finding of the present study was contradictory to several researchers 9,10,11 who found that solvents either reduced or did not affect bonding to dentin. Roberts et al 3 found that usage of EndoSolv R to remove remnants of Ah Plus filled root canal results in bond strength of adhesive resin to coronal dentin equivalent to controls where solvent was not used.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The finding of the present study was contradictory to several researchers 9,10,11 who found that solvents either reduced or did not affect bonding to dentin. Roberts et al 3 found that usage of EndoSolv R to remove remnants of Ah Plus filled root canal results in bond strength of adhesive resin to coronal dentin equivalent to controls where solvent was not used.…”
Section: Discussioncontrasting
confidence: 99%
“…Topçuoğlu et al 10 found that some solvents as chloroform reduced the bond strength of root canal sealer to root canal dentin, while other solvents such as orange oil and Eucalyptol did not influence the bond to root dentin. Guedes et al 11 found that eucalyptol reduced the bond strength of fiber glass post to root dentin. On the other hand, xylene and orange oil did not influence the bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…Shokouhinejad et al 29 demonstrated that the chloroform used in retreatment had an adverse effect on the bond strength of Resilon/Epiphany SE. Guedes et al 30 reported that the use of eucalyptol significantly decreased the bond strength between fiberglass posts and root canal dentin. Further, after endodontic retreatment, the postspace could contain a greater amount of debris than after the initial treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28] However, the effect of retreatment has not been so documented. Few studies have assessed the influence of this procedure on the bonding process, 29,30 despite the fact that retreatment is indicated when the initial procedure fails, 11,12 and therefore merits attention. Shokouhinejad et al 29 demonstrated that the chloroform used in retreatment had an adverse effect on the bond strength of Resilon/Epiphany SE.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it reduces working time and facilitates the insertion of instruments, making this stage of the surgery safer (19,22,26) . Although Xylol was the most effective solution when removing filling material used jointly with rotary or oscillating instruments, most dentists do not use solvents due to their toxic action (27) . In a study conducted by Caetano et al (25) , xylol effectively removed the filling material compared to other solvents and used jointly with passive ultrasonic irrigation (PUI).…”
Section: Developmentmentioning
confidence: 99%